The impact of teacher punishment intensity on parental trust in rural China: an experimental examination of a moderated mediation model - Qi, Chunhui; Guo, Juan; Liu, Yanfeng; Zhang, Zhen; Zhao, Guoxiang (Frontiers in Psychology, 2025)
Pedagogical punishment refers to the educational behavior carried out by teachers to manage, instruct or correct students who violate rules, so as to promote the healthy development of students. In home-school partnerships, parents determine their level of trust in educators based on pedagogical punishment. Preliminary empirical evidence indicates that the punishment intensity impacts parents’ interpersonal trust, though the causal pathways remain to be elucidated. Utilizing a situational experimental design with 462 rural Chinese guardians (234 females, mean age is 40.86 years), this research establishes a causal relationship between pedagogical punishment intensity and parental trust. The analysis further evaluates trustworthiness perception as a mediator and student violation severity as a moderating variable. The findings demonstrate that teacher punishment not only directly strengthens parental trust but also indirectly increases it through perceived trustworthiness. Notably, the severity of student misconduct moderates the relationship between punishment intensity and parental trust, indicating that rigorous punishment behaviors in response to severe violations foster heightened perceived trustworthiness relative to less stringent interventions. This study offers critical insights to education professionals on the rationale and strategies for implementing appropriate punishment practices, thereby enhancing parental trust in educators.